2022
DOI: 10.3390/machines10050317
|View full text |Cite
|
Sign up to set email alerts
|

Review on Motion and Load-Bearing Characteristics of the Planetary Roller Screw Mechanism

Abstract: Studying the motion and load-bearing characteristics of the planetary roller screw mechanism is the basis for the structural design and performance optimisation of the mechanism. The mechanical structures and working principles of different kinds of planetary roller screw mechanisms are summarised. Published papers on kinematic, load-bearing and dynamic models of the planetary roller screw mechanism are reviewed. Based on the slip state in point contacts at the screw–roller and the nut–roller interfaces, the k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 52 publications
0
10
0
Order By: Relevance
“…Yao et al 78 then developed an optimization model for a multi-stage progressive PRSM, achieving a uniform load distribution and reduced contact stresses by considering both rolling-sliding friction and reduced axial clearance. Liu et al 79 presented a technique for thread engagement that relies on the convex and concave nature of threaded teeth, and conducted an investigation into the effects of specific parameters on the engagement gap and load distribution. Based on this, Du et al 80 carried out multi-objective optimization of the model using the feasibility identification method, which demonstrated that the devised model and optimization framework lowered the contact stresses on the threaded teeth.…”
Section: Bearing Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…Yao et al 78 then developed an optimization model for a multi-stage progressive PRSM, achieving a uniform load distribution and reduced contact stresses by considering both rolling-sliding friction and reduced axial clearance. Liu et al 79 presented a technique for thread engagement that relies on the convex and concave nature of threaded teeth, and conducted an investigation into the effects of specific parameters on the engagement gap and load distribution. Based on this, Du et al 80 carried out multi-objective optimization of the model using the feasibility identification method, which demonstrated that the devised model and optimization framework lowered the contact stresses on the threaded teeth.…”
Section: Bearing Characteristicsmentioning
confidence: 99%
“…[22][23][24] Furthermore, the PRSM has been continuously favored by the above fields because of its excellent performance and can effectively solve the bottleneck problems under limited usage space. With the gradual increase of attention to this particular device, although there are specific reviews of the development trend 25 and load-bearing characteristics, 26 a comprehensive analysis regarding the errors and transmission has not yet been reviewed.…”
Section: Introductionmentioning
confidence: 99%
“…PRSMs, as a newer class of actuators, have garnered attention for their high performance in EMA systems. Reviews have systematically examined the structure, advantages, limitations, and applications of various PRSM types [40], and the development of multi-pair dynamic contact and multi-body vibration system models [41]. The review on transmission characteristics [42] explores the kinematic, load-bearing, and dynamic models developed to understand PRSMs' behavior, emphasizing the need for integrated model research that considers detailed nonlinear joints and multi-physics parameters for highfidelity mechanical modeling.…”
Section: Introductionmentioning
confidence: 99%
“…The actuator is an important part of the flap actuation system, which can be divided into pneumatic, hydraulic and electric types according to the driving mode. The EMA has advantages such as light weight, high efficiency, easy maintenance and easy installation, but it also has disadvantages such as its performance being easily affected by energy, loads and nonlinear factors [1][2][3]. The EMA is a multibody system consisting of the motor, controllers, reducer, actuator and sensors, in which the clearance, friction and other nonlinear factors are detrimental to the output characteristics of the system.…”
Section: Introductionmentioning
confidence: 99%